Laminated nonwoven fabrics, laminated electrets, and filters
Patent Information
- Application Number
- JP2025030236
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2026-09-08
AI Technical Summary
【0012】 本発明により、高い捕集効率と低い圧力損失を両立した高い濾過性能を有する積層不織布、積層エレクトレット、これらを用いたフィルター、フィルターユニットを提供することができる。
Smart Images

Figure 2026142938000001 
Figure 2026142938000002
Abstract
Description
[[TECHNICAL FIELD]]
[0001] The present invention relates to a laminated nonwoven fabric, a laminated electret, and a filter using the same. [[BACKGROUND ART]]
[0002] Conventionally, air filters have been used to remove atmospheric dust and the like, and fiber sheets are widely used as filter media. Filters made of these fibrous materials capture particles on fibers through mechanical collection mechanisms such as interception, diffusion, and inertial collision. It is known that when the aerodynamic equivalent diameter of particles to be captured in a practical use environment is about 0.1 to 1.0 μm, the filter collection efficiency has a minimum value, and electret filters utilizing the electrostatic attraction of electrets are used to compensate for this weakness.
[0003] The performances required for an air filter are high collection efficiency and low pressure loss, but high collection efficiency and low pressure loss are in a trade-off relationship, and electret filters are widely used as a method to solve this problem.
[0004] In order to improve the collection efficiency of electret filters, it is known that it is preferable to form an electret by imparting electrostatic charge to a fibrous material by a method of bringing a liquid into contact with or colliding with the fibrous material (liquid contact charging method). For example, as an electret that achieves both cost and performance, there is known an electret obtained by imparting electrostatic charge to a fibrous material formed from a mixture of a resin mainly composed of polyolefin resin with a nitrogen-containing compound such as a hindered amine compound added thereto, by bringing the fibrous material into contact with a liquid such as water.
[0005] Attempts have also been made to simultaneously satisfy both high collection efficiency and low pressure loss by adding a crystal nucleating agent, a charge enhancing additive or the like to a thermoplastic resin, or adding a metal salt to a fiber sheet (see Patent Documents 1 to 3).
[0006] In addition, it has been proposed to increase the gaps between fibers and suppress the increase in pressure loss by forming a nonwoven fabric that mixes fine and thick fibers (see Patent Document 4). [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] Japanese Patent Publication No. 2018-40098 [Patent Document 2] WO2018 / 105546A1 [Patent Document 3] Special Publication No. 2018-523761 [Patent Document 4] Japanese Patent Publication No. 2006-037295 [Patent Document 5] Special Publication No. 2011-506628 [Overview of the project] [Problems that the invention aims to solve]
[0008] In recent years, there has been a demand for improved filtration performance in air filters, such as those for air purifiers and cabin filters, including increased airflow and higher efficiency, and conventional methods are no longer sufficient.
[0009] Therefore, in view of the above problems, the present invention provides a laminated nonwoven fabric, etc., that has high filtration performance that simultaneously satisfies high collection efficiency and low pressure loss, which could not be achieved in the conventional methods. [Means for solving the problem]
[0010] As a result of diligent research by the inventors, we have discovered that by using the following configuration, we can obtain a laminated nonwoven fabric with high filtration performance that simultaneously satisfies high collection efficiency and low pressure loss, and have arrived at the present invention. In other words, the present invention is as follows.
[0011] 1. A laminated nonwoven fabric in which a nonwoven fabric A having constituent fibers a containing a thermoplastic resin is laminated with a nonwoven fabric B having constituent fibers b containing a thermoplastic resin, wherein the average fiber diameter of the constituent fibers b is larger than the average fiber diameter of the constituent fibers a, the average fiber diameter of the constituent fibers a is 0.5 to 5.0 μm, the average fiber diameter of the constituent fibers b is 2.0 to 10 μm, and the proportion of the constituent fibers b contained in the nonwoven fabric B that are less than or equal to the average fiber diameter of the constituent fibers a contained in the nonwoven fabric A is 30% or less. 2. The laminated nonwoven fabric described in 1 above, wherein at least one of the nonwoven fabric A and the nonwoven fabric B contains a nitrogen-containing compound. 3. The laminated nonwoven fabric according to 1 or 2 above, characterized in that both nonwoven fabric A and nonwoven fabric B are long-fiber nonwoven fabrics. 4. A laminated electret obtained by imparting an electric charge to the laminated nonwoven fabric described in item 3 above. 5. A filter or filter unit using the stacked electret described in item 4 above. [Effects of the Invention]
[0012] The present invention provides laminated nonwoven fabrics, laminated electrets, filters, and filter units using these materials, which have high filtration performance while achieving both high collection efficiency and low pressure loss. [Modes for carrying out the invention]
[0013] The present invention will be described in detail below, but the present invention is not limited to the following, and it is possible to implement it with appropriate modifications within the scope that is consistent with the spirit of the preceding and following, and all such modifications are included within the technical scope of the present invention.
[0014] The laminated nonwoven fabric of the present invention is constructed by laminating two nonwoven fabrics with different average fiber diameters of constituent fibers containing a thermoplastic resin. For convenience, the nonwoven fabric with a smaller average fiber diameter will be referred to as nonwoven fabric A, and the nonwoven fabric with a larger average fiber diameter will be referred to as nonwoven fabric B. In other words, the laminated nonwoven fabric of the present invention is a laminated nonwoven fabric in which nonwoven fabric A, which has constituent fibers a containing a thermoplastic resin, and nonwoven fabric B, which has constituent fibers b containing a thermoplastic resin, are laminated together. The average fiber diameter of constituent fibers b is larger than the average fiber diameter of constituent fibers a. In the laminated nonwoven fabric of the present invention, nonwoven fabric A and nonwoven fabric B may be either the first layer (lower layer, back layer) or the second layer (upper layer, surface layer). In the laminated nonwoven fabric of the present invention, the thermoplastic resin contained in constituent fibers a and the thermoplastic resin contained in constituent fibers b may be the same or different.
[0015] The thermoplastic resin used in the present invention may be just one type, or it may be a combination of two or more types that differ in melting point, molecular weight, and crystal structure.
[0016] The thermoplastic resin used in the present invention is not particularly limited, but from the viewpoint of freedom of shape and charge stability of the electret, it is preferably a polyolefin resin that is hydrophobic and has high electrical resistance. Examples of polyolefin resins include homopolymers of olefins such as ethylene, propylene, butylene, hexene, octene, butadiene, isoprene, chloroprene, methyl-1-pentene, and cyclic olefins, or copolymers composed of two or more of the above olefins. One type of polyolefin resin may be selected and used alone, or two or more types may be selected and used in combination. The polyolefin resin preferably contains at least one selected from polyethylene, polypropylene, and polymethylpentene, and more preferably contains polypropylene. The content of polyolefin resin in 100 parts by mass of the laminated nonwoven fabric of the present invention is preferably 80% by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more. The upper limit of the content of polyolefin resin is not particularly limited, for example, 99.5% by mass or less, and preferably 99% by mass or less.
[0017] The melt flow rate (MFR) of the thermoplastic resin used in the present invention is not particularly limited, but it is preferably 1.0 g / 10 minutes or more, more preferably 5.0 g / 10 minutes or more, still more preferably 10 g / 10 minutes or more, and particularly preferably 20 g / 10 minutes or more, when measured at a temperature of 230°C under a load of 2.16 kg in accordance with ASTM D 1238.
[0018] In the present invention, when two or more thermoplastic resins are selected and used in combination, a compatibilizer may be added as necessary from the viewpoint of compatibility. Compatibilizers are used to control the dispersion structure. Examples of such compounds include, as commercial products, Dynaron (registered trademark) 6200P, Kraton (trademark) MD1648, and the like. There are no particular limitations on the compatibilizer, and compatibilizers described in "Plastic Compatibilizers: Development, Evaluation, Recycling" (CMC Publishing) can also be suitably used. Furthermore, these compatibilizers may be used alone or in a mixture of two or more.
[0019] The thermoplastic resin used in the present invention may be derived from fossil raw materials, derived from plants, or a mixture of both, and an advantageous composition can be selected from the viewpoints of availability and life cycle assessment. The term "derived from fossil raw materials" means, as is conventional, that the main component is a component obtained by pyrolyzing naphtha obtained from fossil raw materials typified by petroleum, coal, natural gas, and the like. The term "derived from plants" means that the resin contains carbon derived from plant raw materials. In the case of a mixture of fossil raw material-derived and plant-derived materials, the ratio of the plant-derived raw material can be calculated from the carbon ratio.
[0020] Examples of "plant-derived" thermoplastic resins include plant-derived polyethylene resin, which is a homopolymer of plant-derived ethylene derived from bioethanol obtained from plant raw materials, or a copolymer of said plant-derived ethylene with a small amount of other comonomers. Methods for producing plant-derived ethylene, plant-derived α-olefins, and plant-derived polyethylene resins are described in detail, for example, in Patent Document 5. Examples of commercially available plant-derived polyethylene resins include Green PE manufactured by Braskem SA.
[0021] The nitrogen-containing compound content relative to 100% by mass of the laminated nonwoven fabric of the present invention is 0.1 to 5% by mass, preferably 0.5 to 3% by mass, and more preferably 0.75 to 1.5% by mass. If the nitrogen-containing compound content is lower than 0.1% by mass, the amount of charge will be low, resulting in a decrease in filtration characteristics, and if it is higher than 5% by mass, the stability of the charge will be lost due to increased hygroscopicity. The nitrogen-containing compound may be contained in nonwoven fabric A, in nonwoven fabric B, or in both.
[0022] The nitrogen-containing compound is not particularly limited as long as it provides the desired properties described above, but it is preferably a hindered amine compound containing at least one of a 2,2,6,6-tetramethylpiperidine structure and a triazine structure, and it is more preferably a hindered amine compound containing a 2,2,6,6-tetramethylpiperidine structure and a triazine structure.
[0023] Hindered amine compounds are not particularly limited, but examples include poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}] (Kimasorb® 944LD, manufactured by BASF Japan), dimethyl-1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethyl-4-piperidine polycondensate (Tinuvin® 622LD, manufactured by BASF Japan), and 2-[[3,5-bis(1,1-dimethylethyl)-4-hydroxy Examples include phenylmethyl]-2-butylpropanediate bis[1,2,2,6,6-pentamethyl-4-piperidinyl] (Tinuvin® 144, manufactured by BASF Japan), dibutylamine 1,3,5-triazine·N,N-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,6-hexamethylenediamine·N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine polycondensate (Chimasorb® 2020FDL, manufactured by BASF Japan), and 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(hexyloxy)-phenol (Tinuvin® 1577FF, manufactured by BASF Japan). In particular, it is preferable that the compound contains a 2,2,6,6-tetramethylpiperidine structure and a triazine structure, and more preferably Kimasove® 944LD or Kimasove® 2020FD. One of the above compounds may be used alone as the hindered amine compound, or two or more may be used in combination.
[0024] The nitrogen-containing compound used in this invention preferably has a melting point in the range of 50°C to 300°C, more preferably in the range of 70°C to 280°C, and most preferably in the range of 90°C to 250°C. If the melting point is too low, stickiness and dissipation are likely to occur, and if it is too high, processability may be poor. The thermal decomposition temperature is preferably 150°C or higher, more preferably 200°C or higher, even more preferably 250°C or higher, and particularly preferably 300°C or higher. If the thermal decomposition temperature is low, molding processing conditions and usage environment may be restricted.
[0025] If the laminated nonwoven fabric of the present invention contains a nitrogen-containing compound, it is sufficient that it be present on at least the surface of the molded nonwoven fabric, and it can be introduced by solution coating, powder adhesion, solution mixing with thermoplastic resin, polymerization mixing, melt mixing, etc. The nitrogen-containing compound may be contained in nonwoven fabric A, in nonwoven fabric B, or in both.
[0026] Of the above methods, the melt mixing method is superior in terms of homogeneity and processability. It can be used by directly mixing it with the resin during melt molding into nonwoven fabric, or by using it as is or diluted as a pre-prepared additive masterbatch.
[0027] The laminated nonwoven fabric of the present invention is obtained by laminating two layers of nonwoven fabric obtained using a thermoplastic resin. Here, "using" means that a commercially available thermoplastic resin may be used as is, or, if necessary, a commercially available thermoplastic resin with reduced molecular weight, additives, or other resins may be melt-mixed and used.
[0028] In the manufacturing of the laminated nonwoven fabric of the present invention, the method for laminating the nonwoven fabrics is not particularly limited and can be any conventionally known method that can laminate nonwoven fabrics. For example, methods such as directly fusing the nonwoven fabrics together, fusing the two nonwoven fabrics together by heating and pressing, or bonding them with an adhesive such as a hot melt adhesive or a solvent-based adhesive can be used, but from the viewpoint of filtration performance, the direct fusing method is the most suitable among these. Specifically, it is suitable to directly deposit the second layer of nonwoven fabric on top of the first layer of nonwoven fabric. In this case, the nonwoven fabrics may be spun separately using an apparatus having two nozzles and laminated in one step, or the first layer of nonwoven fabric may be spun using an apparatus having one nozzle, and then the second layer of nonwoven fabric may be spun in the same way and deposited to laminate in two steps.
[0029] In the laminated nonwoven fabric of the present invention, both nonwoven fabric A and nonwoven fabric B are long-fiber nonwoven fabrics. The manufacturing methods for nonwoven fabric A and nonwoven fabric B are not particularly limited and can be manufactured by conventionally known methods, but nonwoven fabrics obtained by the spunbond method, meltblown method, fused electrospinning method, or fused force spinning method are more preferred, and nonwoven fabrics obtained by the meltblown method are particularly preferred from the viewpoint of filtration performance. The manufacturing methods for nonwoven fabric A and nonwoven fabric B may be the same or different.
[0030] The basis weight of the laminated nonwoven fabric of the present invention is not particularly limited, but from the viewpoint of filtration performance, it is 2 to 100 g / m². 2 Preferably, it is 5-80 g / m 2 It is more preferable that the amount be 8-60 g / m 2 It is even more preferable that the amount be 10-40 g / m 2 This is particularly preferable. If the mesh size is too small, it will be difficult to obtain practical filtration performance, and if the mesh size is too large, the pressure loss may become too high.
[0031] The thickness of the laminated nonwoven fabric of the present invention is not particularly limited, but from the viewpoint of filtration performance, it is preferably 0.01 to 2.00 mm, more preferably 0.05 to 1.50 mm, even more preferably 0.10 to 1.00 mm, and particularly preferably 0.20 to 0.50 mm. If the thickness is too small, it may cause an increase in pressure loss, and if it is too large, the voids will become larger and the filtration performance may decrease.
[0032] In the laminated nonwoven fabric of the present invention, the average fiber diameter of the constituent fibers a of nonwoven fabric A is preferably 0.5 to 5.0 μm, more preferably 1.0 to 4.5 μm, and even more preferably 1.5 to 4.0 μm. Similarly, the average fiber diameter of the constituent fibers b of nonwoven fabric B is preferably 2.0 to 10 μm, more preferably 2.5 to 9 μm, and even more preferably 3.0 to 8 μm. As described above, the average fiber diameter of constituent fibers b is greater than the average fiber diameter of constituent fibers a.
[0033] In laminated nonwoven fabrics, it is difficult to obtain practical collection efficiency when the average fiber diameter is greater than 10 μm. Furthermore, when the average fiber diameter is smaller than 0.5 μm, fiber scattering occurs, significantly reducing productivity.
[0034] The fiber diameters described above are determined by using a scanning electron microscope to measure the diameters of 100 fibers each on the back and front surfaces (each nonwoven fabric) of the laminated nonwoven fabric, ensuring no fiber overlap within the same field of view. The average fiber diameter is then calculated using the geometric mean. By measuring from both the back and front surfaces of the laminated nonwoven fabric, the average fiber diameters of nonwoven fabric A and nonwoven fabric B can be calculated separately.
[0035] The laminated nonwoven fabric of the present invention has different average fiber diameters for nonwoven fabric A and nonwoven fabric B. Here, the average fiber diameter of constituent fiber a is used as the reference value, and the proportion of constituent fiber b of nonwoven fabric B that is smaller (thinner) than the reference value is calculated. In the laminated nonwoven fabric of the present invention, this proportion is preferably 40% or less, more preferably 35% or less, and even more preferably 30% or less. By setting the above proportion within the above range, an appropriate amount of void can be obtained due to the density of the fiber diameters, and a low pressure loss can be achieved. Furthermore, by having nonwoven fabric A with a small average fiber diameter, a high collection efficiency can be obtained, and a high filtration performance with a good balance between pressure loss and collection efficiency can be achieved.
[0036] In the laminated nonwoven fabric of the present invention, nonwoven fabric A and nonwoven fabric B can be either the first layer (lower layer, back layer) or the second layer (upper layer, surface layer), and either one can be used whichever is more advantageous in terms of productivity, processability, and filtration performance.
[0037] The basis weight, thickness, and average fiber diameter of the laminated nonwoven fabric of the present invention can be adjusted by conventionally known methods. For example, in the meltblown process, the conveying speed, conveyor angle, collection distance, discharge volume, nozzle pitch, nozzle L / D, resin temperature, hot air temperature, and hot air flow rate can be adjusted.
[0038] The laminated nonwoven fabric of the present invention may contain other polymers, colorants, stabilizers, nucleating agents, and other compounding agents as needed, as long as they do not impair the objectives of the present invention. Examples of components that may be optionally added include conventionally known antioxidants, heat-resistant stabilizers, weather-resistant stabilizers and other stabilizers, slip agents, anti-blocking agents, anti-fogging agents, lubricants, dyes, pigments, natural oils, synthetic oils, and the like. When these compounding agents are added, they may be added to only one of nonwoven fabric A and nonwoven fabric B, or to both.
[0039] The method for electretizing the laminated nonwoven fabric of the present invention by imparting an electric charge is not particularly limited and can be arbitrarily selected from conventionally known charging methods such as liquid contact charging, corona charging, triboelectric charging, field charging, hot field charging, and electron beam irradiation. Liquid contact charging is preferred, as it is possible to obtain an electret with high filtration characteristics using this method. More specifically, it is preferable to bring a liquid into contact with or into contact with the laminated nonwoven fabric by methods such as suction, pressurization, or ejection. The direction in which the liquid contact is made is not particularly limited and may be from nonwoven fabric A to nonwoven fabric B, or vice versa.
[0040] In the liquid contact charging method, the liquid to be contacted or impacted is not particularly limited as long as the desired properties can be obtained, but water is preferred in terms of handling and performance. A liquid obtained by adding a secondary component (a component other than water) to water may be used instead of water, and the conductivity and pH of the liquid can be adjusted by the type and amount of the secondary component added.
[0041] In the liquid contact charging method, the liquid to be contacted or impacted preferably has a pH of 1 to 11, more preferably 3 to 9, and even more preferably 5 to 7. Furthermore, the liquid to be contacted or impacted preferably has an electrical conductivity of 100 μS / cm or less, more preferably 10 μS / cm or less, and even more preferably 3 μS / cm or less.
[0042] Filters and filter units using laminated electrets, which are laminated nonwoven fabrics to which electrostatic charges have been applied, are also included in the scope of the present invention. When the laminated nonwoven fabric of the present invention is used as an electret filter, the filter media quality coefficient (QF) value described later is 1.2 or higher, preferably 1.3 or higher, and more preferably 1.4 or higher. The higher the QF value, the higher the collection efficiency and the lower the airflow resistance, resulting in a high-performance filter. Electrets with a QF value of less than 1.2 have problems such as excessively low collection efficiency or excessively high airflow resistance. The QF value in this specification is a value calculated based on the airflow resistance when air is passed through in the thickness direction at a wind speed of 10.4 cm / s and the number of particles counted by a laser particle counter in the particle size category of 0.3 to 0.5 μm, and is calculated by the following formula. QF value [mmAq] -1 ]=-[ln(1-(particle collection efficiency (%) / 100))] / [airflow resistance (mmAq)]
[0043] When the laminated nonwoven fabric of the present invention is used in an electret filter, the particle collection efficiency at a wind speed of 10.4 cm / s can be adjusted in various ways depending on the required characteristics, but it is preferably 80% or more, more preferably 90% or more, even more preferably 99% or more, and particularly preferably 99.9% or more. The particle collection efficiency described herein is calculated based on the number of particles in the particle size category of 0.3 to 0.5 μm measured by a laser particle counter before and after passing through the filter when air is passed through the filter in the thickness direction at a wind speed of 10.4 cm / s.
[0044] When the laminated electret of the present invention is used as a filter, the airflow resistance at a wind speed of 10.4 cm / s is preferably in the range of 1.0 to 30 mmAq, more preferably 2.0 to 20 mmAq, and particularly preferably 3.0 to 10 mmAq. If the airflow resistance is too low, a dense nonwoven fabric cannot be obtained, resulting in insufficient performance as a filter, and if the airflow resistance is too high, the advantages of the electret filter are lost.
[0045] The laminated electret of the present invention may also be a filter consisting solely of electrets, or a filter made by combining electrets with other materials. The shape of the filter is not particularly limited and may be a sheet-like filter with pleating, corrugation, or other wavy processing.
[0046] When the laminated electret of the present invention is used as a filter, it can be used in combination with other components as needed. That is, the filter of the present invention can be used in combination with a pre-filter layer, a fiber protection layer, a reinforcing member, a functional fiber layer, an adsorbent layer, and the like.
[0047] Examples of pre-filter layers and fiber protection layers include spunbond nonwoven fabrics, thermal bond nonwoven fabrics, and polyurethane foam, while examples of reinforcing members include dry-spun nonwoven fabrics, wet-spun nonwoven fabrics, and various types of nets. Functional fiber layers include antibacterial, antiviral, and colored fiber layers for identification and design purposes, while examples of adsorbent layers include activated carbon and silica gel.
[0048] The laminated nonwoven fabric, laminated electret, and electret filter of the present invention can be used in a wide range of applications. In particular, they can be suitably used as filters for protection of various devices, such as dust masks, dustproof clothing, various air conditioning elements, air purifiers, cabin filters, and other protective equipment, for purposes such as protection, breathability, stain resistance, and waterproofing. [Examples]
[0049] Embodiments of the present invention will be described below. The test method is shown below. (1) Air resistance A sample punched out to 72mmφ is attached to a 50mmφ effective airflow adapter, and a slight differential pressure is applied. A meter was connected to two pipes with an inner diameter of 50 mm, which were linked vertically. Air was passed through the sample in the thickness direction at a wind speed of 10.4 cm / s, and the differential pressure between the top and bottom of the sample without any constriction was measured as the airflow resistance (pressure loss) (mmAq).
[0050] (2) Particle collection efficiency and particle transmission rate A sample punched to 72 mm in diameter was mounted in an adapter with an effective airflow diameter of 50 mm in diameter. Air was passed through the sample in the thickness direction at a wind speed of 10.4 cm / s, and the particle collection efficiency was measured using a light scattering particle counter KC-01E manufactured by Rion Co., Ltd. in the following manner. Particles evaluated: atmospheric dust particles Wind speed: 10.4cm / s Particle collection efficiency [%] = (1 - (Number concentration of particles with a particle size of 0.3 to 0.5 μm after sample transmission ÷ Number concentration of particles with a particle size of 0.3 to 0.5 μm before sample transmission)) × 100 Particle transmittance = (Number concentration of particles with a particle size of 0.3 to 0.5 μm after sample transmission ÷ Number concentration of particles with a particle size of 0.3 to 0.5 μm before sample transmission)
[0051] (3) Filter media quality factor (QF) value Using the values of the air permeability resistance measured in (1) above and the particle transmittance measured in (2) above, the QF value was calculated using the following formula. QF[mmAq -1 ]=-[ln(1-(particle collection efficiency (%) / 100))] / [airflow resistance (mmAq)]
[0052] (4) Inspection Six samples with a diameter of 72 mmΦ were collected, the weight of each sample was measured, the obtained values were converted to a unit area, and the arithmetic mean of these values was rounded to two decimal places.
[0053] (5) Thickness The thickness of each sample whose basis weight was measured was measured using a thickness gauge with a 7g load, and the arithmetic mean of these measurements was rounded to the third decimal place.
[0054] (6) Average fiber diameter Five arbitrary points were selected on both the front and back surfaces of the sample, and the fiber diameter was measured at each point using an electron microscope (n=20). The average fiber diameter was calculated by the arithmetic mean of the 100 fibers measured on each surface. Measuring the back surface allows for the determination of the average fiber diameter of one nonwoven fabric, and measuring the front surface allows for the determination of the average fiber diameter of the other nonwoven fabric. In the case of a single layer, measuring the front and back surfaces demonstrates that there is no significant difference in fiber diameter distribution between the front and back surfaces of the single layer.
[0055] (7) Percentage of constituent fibers of nonwoven fabrics with a large average fiber diameter that is below the standard value The average fiber diameter of the nonwoven fabric with the smaller average fiber diameter (nonwoven fabric A) obtained in (6) above was used as the reference value. For the nonwoven fabric with the larger average fiber diameter (nonwoven fabric B) obtained in (6) above, the proportion of fibers with or less than the reference value was calculated. In the case of a single layer, the average fiber diameter of the side with the smaller average fiber diameter was used as the reference value, and the proportion of fibers with or less than the reference value among the fibers of the side with the larger average fiber diameter was calculated.
[0056] <Example 1> For the first layer of nonwoven fabric, a composition of 98.925% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 1400 g / 10 min, 1% by mass of Chimassorb® 944, and 0.075% by mass of magnesium stearate was used. For the second layer of nonwoven fabric, a composition of 46.350% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 200 g / 10 min, 50% by mass of plant-derived high-density polyethylene resin (biomass content of 90% or more) with a melt flow rate (MFR) of 20 g / 10 min, 1.5% by mass of Kraton® MD1648, 1% by mass of Chimassorb® 944, 0.15% by mass of magnesium stearate, and 1% by mass of Sumirizer® GP was used. These materials were spun using a melt-blown apparatus with two nozzles to obtain a laminated nonwoven fabric in a single process. The first layer was spun at 240°C and the second layer at 280°C. The resulting laminated nonwoven fabric was then subjected to electrostatic charge by passing water with an electrical conductivity of 0.7 μS / cm and pH 6.8 from the second layer to the first layer, followed by air drying at 25°C to obtain a laminated electret. It was evaluated according to (1) to (7) above.
[0057] <Example 2> The first layer of nonwoven fabric consists of 66.350% by mass of petroleum-derived polypropylene resin with melt flow rate (MFR) 200g / 10 min, 30% by mass of plant-derived high-density polyethylene resin (biomass content 90% or more) with melt flow rate (MFR) 20g / 10 min, 1.5% by mass of Kraton® MD1648, 1% by mass of Chimassorb® 944, 0.15% by mass of magnesium stearate, and 1% by mass of Sumirizer® GP. The second layer of nonwoven fabric consists of melt flow rate A laminated nonwoven fabric was obtained in one step by spinning a meltblown apparatus with two nozzles. The composition consisted of 66.350% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 200 g / 10 min, 30% by mass of plant-derived high-density polyethylene resin (biomass content of 90% or more) with a melt flow rate (MFR) of 20 g / 10 min, 1.5% by mass of Kraton® MD1648, 1% by mass of Chimassorb® 944, 0.15% by mass of magnesium stearate, and 1% by mass of Smirizer® GP. The spinning temperature was 280°C for the first layer and 280°C for the second layer. A laminated electret was obtained from the obtained laminated nonwoven fabric in the same manner as in Example 1. It was evaluated according to (1) to (7) above.
[0058] <Example 3> As the first layer of nonwoven fabric, a composition of 98.925% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 1400 g / 10 min, 1% by mass of Chimassorb® 944, and 0.075% by mass of magnesium stearate was used. As the second layer of nonwoven fabric, a composition of 98.925% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 1400 g / 10 min, 1% by mass of Chimassorb® 944, and 0.075% by mass of magnesium stearate was used. These materials were spun using a melt-blown apparatus with two nozzles to obtain a laminated nonwoven fabric in one step. The spinning temperature was 270°C for the first layer and 280°C for the second layer. A laminated electret was obtained from the obtained laminated nonwoven fabric in the same manner as in Example 1. It was evaluated according to (1) to (7) above.
[0059] <Example 4> For the first layer of nonwoven fabric, a composition of 98.925% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 1400 g / 10 min, 1% by mass of Chimassorb® 944, and 0.075% by mass of magnesium stearate was used. For the second layer of nonwoven fabric, a composition of 37.5% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 1400 g / 10 min, 56.425% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 200 g / 10 min, 5% by mass of poly-4-methyl-1-pentene resin with a melt flow rate (MFR) of 180 g / 10 min, 1% by mass of Chimassorb® 944, and 0.075% by mass of magnesium stearate was used. These materials were spun using a melt-blown apparatus with two nozzles to obtain a laminated nonwoven fabric in a single process. The spinning temperature was 280°C for the first layer and 320°C for the second layer. A laminated electret was obtained from the resulting laminated nonwoven fabric in the same manner as in Example 1. It was evaluated according to (1) to (7) above.
[0060] <Example 5> For the first layer of nonwoven fabric, a composition of 98.925% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 1400 g / 10 min, 1% by mass of Chimassorb® 944, and 0.075% by mass of magnesium stearate was obtained by spinning at a spinning temperature of 290°C using a melt-blown apparatus with one nozzle. As the second layer of nonwoven fabric, a composition of 66.350% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 200 g / 10 min, 30% by mass of plant-derived high-density polyethylene resin (biomass content of 90% or more) with a melt flow rate (MFR) of 20 g / 10 min, 1.5% by mass of Kraton® MD1648, 1% by mass of Chimassorb® 944, 0.15% by mass of magnesium stearate, and 1% by mass of Smirizer® GP was directly spun onto the first layer of nonwoven fabric using a melt-blown apparatus with one nozzle at a spinning temperature of 250°C, thereby obtaining a laminated nonwoven fabric in two steps. A laminated electret was obtained from the obtained laminated nonwoven fabric in the same manner as in Example 1. It was evaluated according to (1) to (7) above.
[0061] <Comparative Example 1> A single-layer nonwoven fabric was obtained by spinning a single-nozzle meltblown apparatus at a spinning temperature of 295°C with a composition of 66.350% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 200 g / 10 min, 30% by mass of plant-derived high-density polyethylene resin (biomass content of 90% or more) with a melt flow rate (MFR) of 20 g / 10 min, 1.5% by mass of Kraton® MD1648, 1% by mass of Chimassorb® 944, 0.15% by mass of magnesium stearate, and 1% by mass of Smirizer® GP. A single-layer nonwoven fabric was obtained by passing the obtained single-layer nonwoven fabric through water with an electrical conductivity of 0.7 μS / cm and pH 6.8 to impart an electrostatic charge, and then air-drying at 25°C to obtain a single-layer electret. It was evaluated according to (1) to (7) above.
[0062] <Comparative Example 2> A single-layer nonwoven fabric was obtained by spinning a mixture of 98.925% by mass of petroleum-derived polypropylene resin, 1% by mass of Chimassorb® 944, and 0.075% by mass of magnesium stearate using a melt-blown apparatus with one nozzle at a spinning temperature of 280°C, with a melt flow rate (MFR) of 1400 g / 10 min. A single-layer electret was obtained from the obtained single-layer nonwoven fabric in the same manner as in Comparative Example 1. It was evaluated according to (1) to (7) above.
[0063] <Comparative Example 3> A single-layer nonwoven fabric was obtained by spinning a single-nozzle meltblown apparatus at a spinning temperature of 320°C with a composition of 37.5% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 1400 g / 10 min, 56.425% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 200 g / 10 min, 5% by mass of poly-4-methyl-1-pentene resin with a melt flow rate (MFR) of 180 g / 10 min, 1% by mass of Chimassorb® 944, and 0.075% by mass of magnesium stearate. A single-layer electret was obtained from the obtained single-layer nonwoven fabric in the same manner as in Comparative Example 1. It was evaluated according to (1) to (7) above.
[0064] <Comparative Example 4> As the first layer of nonwoven fabric, a composition of 98.925% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 1400 g / 10 min, 1% by mass of Chimassorb® 944, and 0.075% by mass of magnesium stearate was used. As the second layer of nonwoven fabric, a composition of 98.925% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 1400 g / 10 min, 1% by mass of Chimassorb® 944, and 0.075% by mass of magnesium stearate was used. These materials were spun using a melt-blown apparatus with two nozzles to obtain a laminated nonwoven fabric in one step. The spinning temperature was 320°C for the first layer and 320°C for the second layer. A laminated electret was obtained from the obtained laminated nonwoven fabric in the same manner as in Example 1. It was evaluated according to (1) to (7) above.
[0065] <Comparative Example 5> The first layer of nonwoven fabric consists of 66.350% by mass of petroleum-derived polypropylene resin with melt flow rate (MFR) 200g / 10 min, 30% by mass of plant-derived high-density polyethylene resin (biomass content 90% or more) with melt flow rate (MFR) 20g / 10 min, 1.5% by mass of Kraton® MD1648, 1% by mass of Chimassorb® 944, 0.15% by mass of magnesium stearate, and 1% by mass of Sumirizer® GP. The second layer of nonwoven fabric consists of melt flow rate A laminated nonwoven fabric was obtained in one step by spinning a meltblown apparatus with two nozzles. The composition consisted of 66.350% by mass of petroleum-derived polypropylene resin with a melt flow rate (MFR) of 200 g / 10 min, 30% by mass of plant-derived high-density polyethylene resin (biomass content of 90% or more) with a melt flow rate (MFR) of 20 g / 10 min, 1.5% by mass of Kraton® MD1648, 1% by mass of Chimassorb® 944, 0.15% by mass of magnesium stearate, and 1% by mass of Smirizer® GP. The spinning temperature was 240°C for the first layer and 240°C for the second layer. A laminated electret nonwoven fabric was obtained from the obtained laminated nonwoven fabric in the same manner as in Example 1. It was evaluated according to (1) to (7) above.
[0066] Table 1 shows the measurement results for Examples 1-5, and Table 2 shows the measurement values for Comparative Examples 1-5.
[0067] [Table 1]
[0068] [Table 2]
[0069] Tables 1 and 2 show the following: Examples 1-5 are laminated nonwoven fabrics in which the proportion of constituent fibers with a large average fiber diameter that is below the standard value is 30% or less, resulting in a high filter media quality factor (QF) value. Comparative Examples 1-3 are single-layer nonwoven fabrics in which the density of the fiber diameter cannot be changed, resulting in a high proportion of fibers with a large average fiber diameter that is below the standard value, and a low filter media quality factor (QF) value. Comparative Example 4 is a laminated nonwoven fabric, but the average fiber diameter of the two nonwoven fabrics is almost the same, and the proportion of constituent fibers with a large average fiber diameter that is below the standard value is high, resulting in a low filter media quality factor (QF) value. Comparative Example 5 has a high filter media quality factor (QF) value, but both nonwoven fabrics have a large average fiber diameter, and sufficient collection efficiency is not obtained. [Industrial applicability]
[0070] The laminated nonwoven fabric, laminated electret, electret filter, and filter unit of the present invention achieve both high filtration performance and low pressure loss. Therefore, they can be suitably used as filters in applications such as dustproof clothing, dustproof masks, and air purifiers, and can make a significant contribution to industry. However, the scope of its applications is not limited to those described herein.
Claims
1. A laminated nonwoven fabric is formed by laminating a nonwoven fabric A having constituent fibers a containing a thermoplastic resin and a nonwoven fabric B having constituent fibers b containing a thermoplastic resin. The average fiber diameter of the constituent fiber b is greater than the average fiber diameter of the constituent fiber a. The average fiber diameter of the constituent fiber a is 0.5 to 5.0 μm, and the average fiber diameter of the constituent fiber b is 2.0 to 10 μm. A laminated nonwoven fabric characterized in that the proportion of constituent fibers b contained in the nonwoven fabric B that have an average fiber diameter less than or equal to that of constituent fibers a contained in the nonwoven fabric A is 40% or less.
2. The laminated nonwoven fabric according to claim 1, characterized in that at least one of the nonwoven fabric A and the nonwoven fabric B contains a nitrogen-containing compound.
3. The laminated nonwoven fabric according to claim 1 or 2, characterized in that the nonwoven fabric A and the nonwoven fabric B are long-fiber nonwoven fabrics.
4. A laminated electret characterized by having an electric charge applied to the laminated nonwoven fabric described in claim 3.
5. A filter or filter unit using a stacked electret as described in claim 4.
Citation Information
Patent Citations
Melt-blown non-woven fabric sheet and filtering material by using the same
JP2006037295A
Integrated method for the production of ethylene-butylene copolymer, ethylene-butylene copolymer and use of ethylene and 1-butylene as comonomers supplied from renewable natural raw materials.
JP2011506628A
Electret fiber sheet and air filter medium
JP2018040098A
Electret web with charge enhancing additives
JP2018523761A
Electret fiber sheet
WO2018105546A1